2021
DOI: 10.1080/14737159.2021.1889371
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive circulating tumor DNA analysis enables precision medicine: experimental workflow considerations

Abstract: Introduction: Circulating tumor DNA (ctDNA) has become a relevant biomarker in cancer management, allowing tumor assessment through analysis of minimally invasive liquid biopsies. Applications include screening, diagnostics, monitoring of treatment efficacy and detection of minimal residual disease as well as relapse. The potential of ctDNA analysis is significant, but several biological and technical challenges need to be addressed before widespread clinical implementation. Areas covered: Several clinical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 168 publications
0
15
0
3
Order By: Relevance
“…This is because ddPCR employs absolute quantitation and end-point measurement of lower concentrations of starting material sample input of 1 ng/reaction is possible with varying levels of multiplexing ( Fitarelli-Kiehl et al, 2018 ) and Poisson statistics. In a study by Klega et al, ddPCR paired with NGS in pediatric Ewing’s sarcoma showed that ctDNA levels correlate with treatment response and disease-specific biomarkers ( Klega et al, 2018 ) as ddPCR alone is not sufficient to identify all clinically relevant mutations and it is recommended to complement untargeted approaches ( Andersson et al, 2021 ).…”
Section: Methods Of Circulating Tumor Dna Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because ddPCR employs absolute quantitation and end-point measurement of lower concentrations of starting material sample input of 1 ng/reaction is possible with varying levels of multiplexing ( Fitarelli-Kiehl et al, 2018 ) and Poisson statistics. In a study by Klega et al, ddPCR paired with NGS in pediatric Ewing’s sarcoma showed that ctDNA levels correlate with treatment response and disease-specific biomarkers ( Klega et al, 2018 ) as ddPCR alone is not sufficient to identify all clinically relevant mutations and it is recommended to complement untargeted approaches ( Andersson et al, 2021 ).…”
Section: Methods Of Circulating Tumor Dna Detectionmentioning
confidence: 99%
“…Sensitivities can be limited by the dilution of fragmented ctDNA with normal germline cfDNA ( Sherwood et al, 2016 ). Andersson et al discussed the potential for the lysis of normal blood cells, which may contaminate the sample ( Andersson et al, 2021 ). Plasma samples must typically be centrifuged and separated within 1–4 h of collection.…”
Section: Challenges Of Circulating Tumor Dna Analysis In Childhood Ca...mentioning
confidence: 99%
“…1 involving six random inputs ξ 0 ∼ Ber(r 1 ), ξ 1 ∼ Ber(r 2 ), ξ (1) ∼ Ber(r 3 ), ξ (2) ∼ Ber(r 4 ), ξ (3) , ξ (4) ∼ Ber(r).…”
Section: Multitype Branching Process With Immigrationmentioning
confidence: 99%
“…Finally, libraries are purified and sequenced. lower than 0.1% in clinically relevant samples [1,7,11]. The main source of sequencing noise is due to the polymerase induced errors that occur during library construction and sequencing [5].…”
Section: Introductionmentioning
confidence: 99%
“…The use of unique molecular identifiers (UMIs or UIDs), applied to this type of sequencing, has dramatically improved the results from such technologies. UMIs and UIDs are molecular barcodes, usually short random nucleotide sequences, that are ligated to amplicons or hybridized sequences during library preparation, allowing for a reduction in background signals, and correcting both DNA polymerase-induced errors and uneven amplification when used in combination with deep sequencing [ 65 , 66 ]. There is a wide range of NGS-based technologies performing targeted sequencing through the use of gene panels aimed at mutation detection.…”
Section: Cfnas Technical Applicationsmentioning
confidence: 99%